2019
DOI: 10.1111/1471-0307.12585
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical changes during the creaming reaction in acid curd fresh cheese: Water mobility and forced synaeresis

Abstract: Water mobility changes during a structure building reaction of full‐fat cream cheese were studied by applying low‐resolution nuclear magnetic resonance. A significant decrease in mobility (T2 relaxation times from 148 to 116 ms) was found in the mobile water phase during texture building. Furthermore, the results were compared to forced synaeresis of the same cheese, which was determined by applying a multistep centrifugation method. The plotted forced synaeresis results displayed the inverse shape of the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…After 14 days of storage, it could be observed that T 21 decreased significantly and the population in T 22 migrated and became undetectable in the control ( p < 0.05). This was probably due to the intense proteolysis leading to an alteration in protein structure as well as a destruction of the protein network [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…After 14 days of storage, it could be observed that T 21 decreased significantly and the population in T 22 migrated and became undetectable in the control ( p < 0.05). This was probably due to the intense proteolysis leading to an alteration in protein structure as well as a destruction of the protein network [ 32 ].…”
Section: Resultsmentioning
confidence: 99%